Pengelolaan Sarana Prasarana Pendidikan Taman Kanak - Kanak Aisyiyah (Studi Komparatif TK Aisyiyah I dan II Desa Pandeyan Ngemplak Boyolali 2015/2016) - Murniwati, Ninuk; , Prof. Dr. Bambang Sumardjoko; , DR. Waston, M.Hum (2016)
The aims of this study are to describe the educational facilities management of Taman Kanak-kanak Aisyiyah which is located in Pandeyan, Ngemplak, Boyolali in academic year 2015/2016, to get a better knowledge related to educational facilities management to the researcher particularly and readers commonly and to give positives contibution to the school. The methodology used in the research is comparative qualitative. The subject in this research is divided into 3 categories. Those are 1) Primer data relates to the observation method and direct interview to the school's principal. 2) Secondary data is the supporting data that got from the document or archive and 3) Library data used to arrage, clarify and strengthen the concept. The data collection techniques are (a) Observation method is done by monitoring, In this method the researcher contributed or seen in the research object situation (b) Interview is delivering the questions directly (c) Documentation includes notes, documents as the data source such as pictures, graphics, photos and verbal things (d) Data validation test which means the result could be declared as valid data when there is no different between reported data and the object of research real data and (e) data analysis process is finding and arranging the data systematically that got from the interview and field notes. The research results of the educational facilities nagement of Taman Kanak-kanak Aisyiyah which is located in Pandeyan, Ngemplak, Boyolali in academic year 2015/2016 are that (1) Planning: TK Aisyiyah Pandeyan uses long-term period (2) Provisioning : TK Aisyiyah I Pandeyan held a discussion to reach an agreements with students' parents, at TK Aisyiyah II independently, this provisioning includes both intern and extern educational facilities (3) tribution: TK Aisyiyah I and II involve the human resources inside and outside the schools (4) Utilizing: TK Aisyiyah I and II are shared used, It means that there is no certain schedule (5) Maintenance: TK Aisyiyah I and II is equal to the classroom's situation, the different is there is the building at TK Aisyiyah II (6) Inventaris : TK Aisyiyah I and II is the same, It includes records-keeping and report and (7) Throwing : TK Aisyiyah I and II is mostly same, the old facilities will be recycled if it is possible, but it will be changed if it is not ossible to be fixed.